Hospital-Based Cancer Registry - Naqqash Adnan , Gohr Rasheed ,SehrishNadeem , Iqra Kanwal , Umer Fayyaz , RaheelAhmed ,Munazza Aziz , Sajid Mehmood , Syed WaqasHassan , Natasha Arzoo , Kashif Adnan , Maryam Iftikhar , Jahangir Sarwar Khan, (Journal of Rawalpindi Medical College, 2017)
Background :. To determine the frequency of different types of malignancies in different gender and age groups, presenting at a surgical unit. Methods: In this observational study cancer patients of both genders were included to determine frequencies of different malignancies that presented to a surgical unit. All the patients with age greater than 12 years and being admitted in surgical unit 1 with the diagnosis of malignancy, were included. The variables recorded included age, sex, address, diagnosis, biopsy, date of biopsy, treatment timeline, stage at presentation, final outcome and referral to other care units. Data was entered and analyzed using the statistical package for social sciences (SPSS) software, version 22. Results: A total of 150 malignant tumours were analyzed. There were 50 (33.3%) male patients and 100 (66.7%) females. Malignant tumours of breast 67 (44.7%) and esophagus 16 (10.7%), were found to be the most common whereas malignant melanoma (0.7%), submandibular tumours (0.7%), and parotid tumours (0.7%), were least common. The most common malignancy in males were of stomach (16.0%) and rectum (16.0%), whereas in females it was the breast malignancies (67.0%). Dividing the age distribution of the patients into 15-year bands, the peak age-category was 41-60 years (46.0%), while only 3 (2.0%) patients were above 80 years. Conclusion: Cancer trends were found to be similar as that of other studies in Pakistan with a few differences. Data management is sub optimal. There is a dire need of integrated system of Cancer Registry.